Drug conjugates—an emerging approach to treat breast cancer. Issue 4 (5th July 2018) - Hasan, Mahmud; Leak, Rehana K.; Stratford, Robert E.; Zlotos, Darius P.; Witt‐Enderby, Paula A.
Abstract: Breast cancer treatment using a single drug is associated with a high failure rate due, in part, to the heterogeneity of drug response within individuals, nonspecific target action, drug toxicity, and/or development of resistance. Use of dual‐drug therapies, including drug conjugates, may help overcome some of these roadblocks by more selective targeting of the cancer cell and by acting at multiple drug targets rather than one. Drug‐conjugate approaches include linking drugs to antibodies (antibody‐drug conjugates), radionuclides (radioimmunoconjugates), nanoparticles (nanoparticle‐drug conjugates), or to other drugs (drug‐drug conjugates). Although all of these conjugates might be designed as effective treatments against breast cancer, the focus of this review will be on drug‐drug conjugates because of the increase in versatility of these types of drugs with respect to mode of action at the level of the cancer cell either by creating a novel pharmacophore or by increasing the potency and/or efficacy of the drugs' effects at their respective molecular targets. The development, synthesis, and pharmacological characteristics of drug‐drug conjugates will be discussed in the context of breast cancer with the hope of enhancing drug efficacy and reducing toxicities to improve patient quality of life.